British and American Representations of 9/11 Literature, Politics and the Media - Gheorghiu, Oana-Celia (Springer International Publishing, 2018)
This book argues that twenty-first-century neorealist fiction is inspired by political and journalistic discourses and, along with them, constitutes one of the many representations of the attacks on September 11 and their outcomes. Adopting a neorealist stance, this book is placed at the intersection of realism and fiction, with often reference to what is perceived as objective writing (media and political texts), not at all so divorced from the practice of literary writings on the event that shook the world on September 11, 2001.